Principle and strategy of using probabilistic shaping in a flexible coherent passive optical network without optical amplifiers - Xing, Sizhe; Li, Guoqiang; Yan, An; Shen, Wangwei; Li, Zhongya; Wang, Jiaye; Shi, Jianyang; He, Zhixue; Chi, Nan; Zhang, Junwen (Journal of optical communications and networking, 2023)
The coherent passive optical network (CPON) has received a great deal of attention in recent years due to its superior receiver sensitivity and extended power budget for 100G and beyond. In order to fully utilize the channel capacity and achieve adaptive rate adjustment in a flexible coherent passive optical network (FLCS-CPON), constellation-shaping techniques, such as probabilistic shaping (PS), have been introduced. Unlike long-distance transmission networks, which are subject to average power constraint when optical amplifiers are utilized, commercial passive optical network systems are generally subject to peak power constraint, as no optical amplifiers are used. This difference makes the classical probabilistic-shaping (CPS) technology less efficient in CPON systems without optical amplifiers. In this study, the use cases of PS in a flexible coherent access network, including nonlinear-penalty-dominant and noise-dominated regions, are thoroughly explored. By fixing the modulation order and utilizing CPS and reversed probabilistic shaping with a fixed modulation format, a hybrid PS-based FLCS-CPON without optical amplifiers is demonstrated, achieving a peak rate of 200G and a high dynamic range boost of up to 72% from 16 to 27.5 dB in upstream burst-mode-based PS-16 quadrature amplitude modulation. Over the entire dynamic range, the net data rate varies from 168 to 85 Gbps with a power budget of 37 dB, and a dynamic range and net-rate product improvement of 55% is achieved.